The Impact of the Precautionary Principle on the Circular Economy Objectives of End-of-Waste in the EU - Sjöblom, Kamilla (My University, 2023)
The precautionary principle is one of the key principles guiding the EU environmental policy mentioned in the TFEU. The precautionary principle must be taken into consideration in End-of-Waste (EoW) practice as well. One of the main environmental objectives of the EU is the shift to circular economy (CE), and utilization of EoW is one of the policy options for supporting that shift. After waste material has completed the EoW procedure, its status as waste ceases and the material is legally seen as a product again. The conditions for material to complete the EoW procedure have been laid out in Article 6 of the amended Waste Framework Directive. This study will focus on the fourth criterion, according to which the use of the substance or object that has completed the EoW procedure must not lead to overall adverse environmental or human health impacts. The precautionary principle becomes part of the EoW assessment due to the fourth criterion. In addition, risk analysis becomes a central topic of discussion, as the presence of adverse impacts is determined in the analysis. The study aims to examine how the precautionary principle affects the CE objectives which the use of EoW targets to promote. The study is executed by using an approach of combining multiple methods. Important sources are CJEU rulings, Commission Communications, legal literature and literature on risks and the concept of scientific certainty. In the study, EoW is used as example of the wider scale impacts that the precautionary principle may have on the CE objectives of EU. The subject is relevant especially from the point of view of evaluating whether the EU environmental policy objectives are achieved. A central conclusion of the study is that the precautionary principle has a two-fold role – it is both a prerequisite for achieving of the CE goals, and a potential barrier for the promotion of CE, if its scope of application is too wide and threshold for its application too low. It is important to execute a comprehensive risk analysis, where both the environmental disadvantages of both cessation and continuation of waste status are compared. Extensive evaluation of risk trade-offs, executed between action and inaction, is a key element of the assessment of adverse environmental impacts, and it is only after such analysis when the precautionary principle can be utilized in the best possible way in environmental risk management.

Ennalta varautumisen periaate on yksi keskeisistä Euroopan unionin toiminnasta tehdyssä sopimuksessa mainituista ympäristöoikeutta ohjaavista periaatteista. Ennalta varautumisen periaate tulee ottaa huomioon myös jätteeksi luokittelun päättymismenettelyssä (EoW). EoW-menettelyä voidaan hyödyntää kiertotalouteen siirtymisessä, joka on yksi keskeisistä EU:n ympäristötavoitteista. Jätemateriaalin käytyä läpi EoW-menettelyn, sen jätestatus lakkaa ja jätteestä tulee lain silmissä taas tuote. Jätteeksi luokittelun päättymisen edellytykset on määritelty uudistetun jätepuitedirektiivin artiklassa 6. Tutkimuksessa tarkastellaan erityisesti kyseisten edellytysten neljättä kriteeriä, jonka mukaisesti EoW-menettelyn läpikäyneen aineen tai esineen käytöstä ei saa aiheutua haitallisia kokonaisvaikutuksia ympäristölle eikä ihmisten terveydelle. Ennalta varautumisen periaate nivoutuukin EoW-menettelyyn nimenomaan artiklan 6 neljännen kriteerin kautta. Keskeiseksi tarkastelun kohteeksi nousee myös riskianalyysi, jossa arvioidaan haitallisten kokonaisvaikutusten olemassaoloa. Tutkimus pyrkii selvittämään, miten ennalta varautumisen periaatteen soveltaminen vaikuttaa niihin kiertotaloustavoitteisiin, joita jätteeksi luokittelun päättymisellä pyritään edistämään. Tutkimuksessani käytän monimetodillista lähestymistapaa. Keskeisiä lähteitä ovat EUTI:n ratkaisut ja komission kommunikaatiot, sekä oikeustieteellinen ja laajemmin riskeihin ja tieteelliseen varmuuteen liittyvä kirjallisuus. Tutkimuksessa jätteeksi luokittelun päättymistä hyödynnetään esimerkkinä ennalta varautumisen periaatteen vaikutuksesta laajemmin EU:n kiertotaloustavoitteiden toteutumiseen. Aihe on tärkeä ensisijaisesti EU:n ympäristöllisten toimenpidetavoitteiden toteutumisen arvioinnin kannalta. Tutkimuksen johtopäätöksenä nousee esiin ennalta varautumisen periaatteen keskeisyys yhtäältä kiertotalouden tavoitteiden toteutumisen varmistamisen kannalta, että sen mahdollinen jarruttava vaikutus, mikäli sitä sovelletaan liian laajasti ja matalalla kynnyksellä. Keskeistä olisikin suorittaa kattava riskianalyysi, jossa otetaan huomioon sekä jätestatuksen loppumisesta, että sen jatkumisesta aiheutuvat ympäristölliset haitat. Kattava riskien punninta, joka tehdään toiminnan ja toimimatta jättämisen välillä, on keskeinen osa haitallisten ympäristöllisten kokonaisvaikutusten arvioinnissa, ja vain sellaisen arvioinnin pohjalta ennalta varautumisen periaatetta on mahdollista hyödyntää parhaalla mahdollisella tavalla ympäristöriskien hallinnassa.
Keywords: end-of-waste, precautionary principle, circular economy